Argument Strength and the Persuasiveness of Stories. Issue 4 (19th May 2018) - Schreiner, Constanze; Appel, Markus; Isberner, Maj-Britt; Richter, Tobias
ABSTRACT: Stories are a powerful means to change people's attitudes and beliefs. The aim of the current work was to shed light on the role of argument strength (argument quality) in narrative persuasion. The present study examined the influence of strong versus weak arguments on attitudes in a low or high narrative context. Moreover, baseline attitudes, interindividual differences in working memory capacity, and recipients' transportation were examined. Stories with strong arguments were more persuasive than stories with weak arguments. This main effect was qualified by a two-way interaction with baseline attitude, revealing that argument strength had a greater impact on individuals who initially were particularly doubtful toward the story claim. Furthermore, we identified a three-way interaction showing that argument strength mattered most for recipients who were deeply transported into the story world in stories that followed a typical narrative structure. These findings provide an important specification of narrative persuasion theory.